The Development of Authentic Personality With Limitations Of The Educational System (in the examples of films: Professor Vujić’s Hat, directed by Z. Šotra, and Dead Poets Society, directed by P. Weir) - JARANOVIĆ, JELENA (Journal of Education Culture and Society, 2020)
This paper focuses on the urge of young people to find a purpose in their lives and make them more meaningful by insisting on the uniqueness of every individual. It is ba-sed on the analysis of two films: Professor Kosta Vujić’s Hat (directed by Zdravko Šotra, 2012; based on the novel by MilovanVitezović) and Dead Poets Society (by Peter Weir, 1989). This journey is made through resisting and  ghting against rigid rules of the educational system. The metamorphosis is infiluenced by two extraordinary teachers who give their students motivation and support. We will also consider the role of a teacher in the modern society and the possibility to switch from an ordinary lecturer to an exceptional leader, who encourages these students to look at life from different perspectives by making them question common thinking patterns.